On-Site Solid Waste Handling Practice and Associated Factors among Condominium Residents in Gondar City, Northwest Ethiopia, 2021: A Community-Based Cross-Sectional Study. (28th January 2023) - Shiferaw, Alemtshay; Tsega, Nuhamin Tesfa; Alemu, Amare; Endalew, Mastewal; Bitew, Bikes Destaw
Abstract : Background . Solid waste is one type of waste that is released from human day-to-day activities and it is considered useless or unwanted for further use. Population growth, rapid urbanization, a booming economy, and an increase in the standards of living of the community have substantially enhanced the rate of solid waste generation in developing countries. Solid wastes can be used as a resource for industrial production or energy generation. However, it causes environmental and human health problems due to poor management. There is scanty information about on-site solid waste management practice in the study area. Therefore, assessing on-site solid management practices and their associated factors, especially for condominium residents is very important. Objective . To assess on-site solid waste handling practice and its associated factors among condominium residents in Gondar city, northwest Ethiopia, 2021. Methods . A community-based cross-sectional study was conducted from March 1 to June 15/2021 among condominium residents in Gondar city. The study included a total of 450 condominium households, with a 99.3% response rate. A binary logistic regression model was used to assess the association between dependent and independent variables. Those variables which have a p value <0.25 in the bivariate analysis were entered into a multivariable logistic regression model. A p value of less than 0.05 with 95% CI was considered a statistically significant factor. Result . In this study, 79.8% with 95% CI (76.4%, 83.3%) of condominium residents had poor on-site solid waste handling practices. The finding also showed that 42.2% and 50.2% of study participants have favorable attitudes and good knowledge towards on-site solid waste handling practices, respectively. In multivariable logistic regression analysis, male household heads (AOR = 1.90; 95% CI, 1.11–3.28), large family size (AOR = 1.87; 95% CI, 1.03–3.40), negative attitude towards on-site solid waste handling practices (AOR = 1.79; 95% CI, 1.07–3.00), not receiving training (AOR = 3.40; 95% CI, 1.77–6.55), and not having legal enforcement (AOR = 2.85; 95% CI, 1.39–5.84) were significantly associated with on-site solid waste handling practices. Conclusion . The on-site solid waste handling practice of condominium households was very poor. The provision of training and enforcement of rules regarding solid waste handling is necessary.